Neuro-ophthalmologic Findings in Visual Snow Syndrome - Yoo, Yung-Ju (J Clin Neurol, 2020)
BACKGROUND AND PURPOSE: The findings of ophthalmic examinations have not been systematically investigated in visual snow syndrome. This study reviewed the abnormal neuro-ophthalmologic findings in a patient cohort with symptoms of visual snow syndrome. METHODS: We retrospectively reviewed 28 patients who were referred for symptoms of visual snow to a tertiary referral hospital from November 2016 to October 2019. We defined the findings of best corrected visual acuity (BCVA), visual field testing, pupillary light reflex, contrast sensitivity, full-field and multifocal electroretinography, and optical coherence tomography. RESULTS: Twenty patients (71%) were finally diagnosed as visual snow syndrome. Their additional visual symptoms included illusionary palinopsia (61%), enhanced entoptic phenomenon (65%), disturbance of night vision (44%), and photophobia (65%). A history of migraine was identified in ten patients (50%). The mean BCVA was less than 0.1 logarithm of the minimum angle of resolution, and electrophysiology showed normal retinal function in all patients. Contrast sensitivity was decreased in two of the seven patients tested. Medical treatment was applied to five patients which all turned out to be ineffective. Among the eight patients who were excluded, one was diagnosed with rod-cone dystrophy and another with idiopathic intracranial hypertension. CONCLUSIONS: Neuro-ophthalmologic findings are mostly normal in patients with visual snow syndrome. Retinal or neurological diseases must be excluded as possible causes of visual snow.